Self-Efficacy, Competence in Technology Information and Computers, and Burnout: What is the Profile for Teachers? - Handayanto, Agung; Miyono, Noor; Yulianti, Padmi Dhyah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Burnout in teachers will affect the teacher's mental health condition. Teacher burnout is rarely researched because it affects teacher credibility. Thus, burnout experienced by teachers must be anticipated because it will be detrimental to the teacher himself, the organization, and the students. Teachers’ self-efficacy and ICT competency are thought to influence teacher burnout. Teachers with low self-efficacy and ICT Competence will tend to be susceptible to burnout. The problem formulation in this research is “Do self-efficacy and ICT Competence have a relationship with teacher burnout?”. This research examines the relationship between self-efficacy and ICT Competence and burnout in teachers. The research uses a quantitative design with SPSS-assisted multiple linear regression. The research results showed an influence of self-efficacy on burnout, an influence of information and computer technology competence on burnout, and an influence of self-efficacy and information and computer technology competence on burnout. Researchers discussed and provided in-depth suggestions for this research.